Advances in Understanding the Immune Imbalance between T-Lymphocyte Subsets and NK Cells in Recurrent Spontaneous Abortion - Zhao, Xiaoxuan; Jiang, Yuepeng; Wang, Lin; Li, Zhihao; Li, Qiang; Feng, Xiaoling (Geburtshilfe und Frauenheilkunde, 2018)
Recurrent spontaneous abortion is a global problem, and unexplained recurrent abortion triggered by immunological factors is an important focus of current research. Helper T lymphocytes (Th cells) and regulatory T lymphocytes (Treg cells) are central in human immune regulation and play a complex role in pregnancy. Natural killer cells (NK cells) exist in the endometrium and cooperate with T lymphocytes to create immune tolerance at the maternal-fetal interface, which is essential for successful pregnancy. This review has analyzed studies on Th17 cell, Treg cell and NK cell dysfunction and cellular imbalances which may contribute to unexplained recurrent spontaneous abortion to suggest a possible direction for future immunotherapies.
Keywords: Th17 cells; Treg cells; decidual natural killer cells; recurrent spontaneous abortion; review